2013
DOI: 10.1055/s-0033-1344217
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and efficiency of a new 22G core needle: a prospective comparison study

Abstract: FNB with the new 22G core needle was technically feasible, efficient and comparable to FNA with a standard needle. The core needle required fewer passes to provide an adequate sample, offering potentially shorter procedure time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
99
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(114 citation statements)
references
References 17 publications
11
99
2
Order By: Relevance
“…Based on all these premises, in the last decade, alternative sampling techniques and dedicated needles to obtain core tissue biopsy specimens for histological examination under EUS guidance have been used and developed [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. In particular, studies using standard 19G needles with or without the stylet have reported very high success rates of tissue acquisition in different patient populations [16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on all these premises, in the last decade, alternative sampling techniques and dedicated needles to obtain core tissue biopsy specimens for histological examination under EUS guidance have been used and developed [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. In particular, studies using standard 19G needles with or without the stylet have reported very high success rates of tissue acquisition in different patient populations [16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, studies using standard 19G needles with or without the stylet have reported very high success rates of tissue acquisition in different patient populations [16][17][18][19][20][21]. Moreover, the Procore TM needles specifically designed to obtain histological samples have been developed and studies using the 19G and the 22G Procore TM have provided excellent results [22][23][24][25]. In the search for a needle able to balance the ability to acquire tissue core biopsy specimens with the easy usability, which would permit its utilization by the large majority of endosonographers, a 25G Procore TM needle with the same reverse bevel technology has also been developed [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22G and 25G ProCore needles are also available, which facilitate transduodenal sampling. Three recent randomized trials comparing the 22G or 25G ProCore needles to standard FNA needles in pancreatic masses and peripancreatic lymphadenopathy [2123] have concluded that there is no significant difference in establishing a correct diagnosis between needles. In a study using the 25G ProCore needle, while a cytological diagnosis was established in 96% of 50 patients, histological core tissue was procured in only 32% of patients [22].…”
Section: Needle Selectionmentioning
confidence: 99%
“…Studies in pancreatic lesions and lymphadenopathy have found similar diagnostic yields to aspiration needles, but may require fewer passes. [3944] There are no published studies specifically evaluating ProCore needles to establish a diagnosis of subepithelial lesions or GIST, although one series included 13 patients with gastric subepithelial lesions established the feasibility of the approach. [45]…”
Section: Biopsy Needlesmentioning
confidence: 99%